2020
DOI: 10.3389/frai.2020.00038
|View full text |Cite
|
Sign up to set email alerts
|

Toward “English” Phonetics: Variability in the Pre-consonantal Voicing Effect Across English Dialects and Speakers

Abstract: Recent advances in access to spoken-language corpora and development of speech processing tools have made possible the performance of "large-scale" phonetic and sociolinguistic research. This study illustrates the usefulness of such a large-scale approach-using data from multiple corpora across a range of English dialects, collected, and analyzed with the SPADE project-to examine how the pre-consonantal Voicing Effect (longer vowels before voiced than voiceless obstruents, in e.g., bead vs. beat) is realized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Sonderegger (2023, 10.3) shows examples, using phonetic data, for frequentist mixed-effects models (using lme4). Tanner et al (2020b) examines the predicted effect of following consonant voicing on vowel duration across 30 English dialects, by extracting from a Bayesian linear mixed-effects model the predicted effect, with 95% credible intervals, for each dialect.…”
Section: Model Predictions Involving Random Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonderegger (2023, 10.3) shows examples, using phonetic data, for frequentist mixed-effects models (using lme4). Tanner et al (2020b) examines the predicted effect of following consonant voicing on vowel duration across 30 English dialects, by extracting from a Bayesian linear mixed-effects model the predicted effect, with 95% credible intervals, for each dialect.…”
Section: Model Predictions Involving Random Effectsmentioning
confidence: 99%
“…For example, Sonderegger et al (2023) show that production of /s/ is more variable than /S/ across English speakers by using the posterior distribution over random-effect variances capturing the degree of by-speaker variability in the spectral peak of each sound. Similarly, Tanner et al (2020b) shows that dialects differ more than speakers (within-dialect) in the effect of consonant voicing on vowel duration by comparing the by-dialect and by-speaker variances.…”
Section: Model Predictions Involving Random Effectsmentioning
confidence: 99%
“…Variation in pronunciation can be observed based on regional dialects, social class, ethnic backgrounds, and individual speech communities. Different sociolinguistic groups may exhibit specific patterns of consonant pronunciation, leading to variation and distinct accents (Tanner et al, 2020). d. Individual Factors: Individual factors refer to the idiosyncratic differences in consonant pronunciation among speakers.…”
Section: Influences On Consonant Pronunciationmentioning
confidence: 99%
“…Tanner et al. (2020) used multiple force‐aligned English corpora and found dialectal differences in vowel lengthening before voiced word‐final obstruents. Finally, as mentioned above, Coto‐Solano et al.…”
Section: Examples Of Computational Sociophonetic Researchmentioning
confidence: 99%
“…professional recorders vs. smartphones and iPads). Tanner et al (2020) used multiple force-aligned English corpora and found dialectal differences in vowel lengthening before voiced word-final obstruents. Finally, as mentioned above, Coto-Solano et al ( 2021) provide evidence that fully automated sociolinguistic analysis is possible: They used ASR to transcribe speech from 352 English speakers.…”
Section: Examples Of Computational Sociophonetic Researchmentioning
confidence: 99%